STRATEGI PENINGKATAN RESILIENSI MASYARAKAT PESISIR TERHADAP TEKANAN SOSIO-EKOLOGIS (Studi Kasus Pesisir Kota Semarang) - Agus Susanto (LPPM Universitas Terbuka, 2017)
Popularity of the Coastal of Semarang city coused of rob that has occurred since the 1970s, and lately getting worse in terms of both area and time (duration) puddle. This is the result of global warming impact on sea level rise. In addition, the coastal city of Semarang was under pressure socio-ecological form of floods, land use, soil degradation, water use conflicts and water pollution. As for the most vulnerable population exposed to pressures socio-ecological are: fishermen / farmers, factory workers, employees, and services. Based on these reasons, done the research resilience of communities from coastal of Semarang city with the aim of knowing the forms of resilience and treatment strategies based on the dimensions of sustainability (ecological, economic and social). The method used is descriptive explorative, data collection with quantitative and qualitative approaches. Analysis of the data used were: descriptive, vulnerability and resilience refers to the IPCC (2001), whereas the strategy to improve resilience using Multi Criteria Decission Making (MCDM) with weighting. The result of analysis is, there are, 3 (three) options strategies for improving resilience, namely: (a) the development of human resources (HR) is through community empowerment, (b) provision of incentives that can be done directly in the form of assistance, and indirectly in the form of regulating the use land, the improvement of facilities and infrastructure, as well as the improvement of social infrastructure, and (c) the manufacture dike embankment can be making a dike in the side of the river and the elevation of the road that can touch on the fundamental aspects of the physical and ecological. Pesisir Semarang populer karena rob yang sudah terjadi sejak tahun 1970an, dan akhir-akhir ini bertambah parah baik dari segi luasan maupun waktu (durasi) genangannya. Hal ini akibat pemanasan global yang berdampak pada kenaikan permukaan laut. Disamping itu, pesisir Kota Semarang mengalami tekanan sosio-ekologi yang berupa: banjir, alih fungsi lahan, penurunan tanah, konflik penggunaan air, dan pencemaran perairan. Adapun kelompok masyarakat yang rentan terpapar tekanan sosio-ekologi adalah: nelayan/petani, buruh pabrik, karyawan, dan jasa. Untuk itu dilakukan penelitian Resiliensi (ketahanan) masyarakat pesisir Kota Semarang dengan tujuan mengetahui bentuk-bentuk resiliensi dan strategi penanganan berdasarkan dimensi keberlanjutan (ekologi, ekonomi, dan sosial). Metode yang digunakan adalah deskriptif eksploratif, pengambilan data dengan pendekatan kuantitatif dan kualitatif. Analisis data yang digunakan adalah: deskriptif, kerentanan, dan resiliensi yang mengacu pada IPCC (2001), sedangkan untuk strategi peningkatan resiliensi menggunakan Multi Criteria Decission Making (MCDM) dengan pembobotan. Hasil analisis: terdapat 3 (tiga) pilihan strategi peningkatan resiliensi yaitu: (a) pengembangan sumberdaya manusia (SDM), yaitu melalui pemberdayaan masyarakat, (b) pemberian insentif yang dapat dilakukan secara langsung, yaitu berupa pemberian bantuan dan tidak langsung yang berbentuk pengaturan penggunaan lahan, peningkatan sarana dan prasarana, serta perbaikan infrastruktur sosial, dan (c) pembuatan tanggul, dapat berupa pembuatan tanggul di sisi sungai dan peninggian jalan yang dapat menyentuh aspek mendasar pada sisi fisik dan ekologis.